Notes relating to the Flora of Bhutan: XVI. Cromapanax lobatus, a new genus and species from Bhutan - Grierson, A. J. C. (Edinburgh Journal of Botany, 2010)
Cromapanax lobatus Grierson, gen. et sp. nov. (Araliaceae) is described from Gaylegphug district, southern Bhutan. Its differences with the allied genus Macropanax are outlined, and some notes on ecology given.